Relationship between the mean of 24-h venous blood glucose and in-hospital mortality among patients with subarachnoid hemorrhage: A matched cohort study - Wang, Jun-Hong; Li, Hua; Yang, Hong-Kuan; Chen, Ru-Dong; Yu, Jia-Sheng (Frontiers in Neurology, 2022)
Abstract Objectives: The purpose of this study was to investigate the association between the mean of 24-h venous blood glucose (BG) and in-hospital mortality in critically ill patients with subarachnoid hemorrhage (SAH). Methods: This was a retrospective cohort study, in which detailed clinical data were extracted from Medical Information Mart for Intensive Ⅳ Care database. The receiver operating characteristic (ROC) curve was used to determine the optimal cut-off value for mean BG. The prognostic value of mean BG was analyzed by univariate and multivariate logistic regression analysis models. Further, the propensity score matching (PSM) analysis was performed to improve the reliability of results by reducing the imbalance across groups. Results: There were a total of 1230 subjects who passed the screening process and entered the subsequent analysis. The generalized additive model revealed a U-shaped relationship between mean BG and in-hospital all-cause mortality. Kaplan-Meier analysis showed that the in-hospital mortality in the high BG group was superior to those in the low BG group (p< 0.05). Multivariable logistic regression showed that a high level of mean BG was an independent risk factor for in-hospital mortality after adjusting for covariates (BG≥ 152.25 mg/dL vs BG<152.25 mg/dL: OR, 95% CIs: 2.689, 1.933-3.739, p<0.001). Similar results were found in the PSM cohort. There was no interaction among various subgroups, and high mean BG was still associated with adverse clinical outcomes in patients with SAH. Conclusion: Our data suggest that mean BG was an independent risk factor for the prognosis of SAH patients. More studies were needed to further analyze the role of the mean of 24-h venous BG in SAH patients.